Description of a new species of the Lissochlora albociliaria species group (Lepidoptera: Geometridae, Geometrinae) - Viidalepp, Jaan; Lindt, Aare (Zootaxa, 2019)
The genus Lissochlora was described by Warren (1900) and revised by Pitkin (1993) with respect to the fauna of Costa Rica. Lissochlora has a small spur or kink to its aedeagus and is distinguished from related genera by the absence of basal costal process of the valva in the male genitalia, which is present in Nemoria Hübner, Rhodochlora Warren and Paromphacodes Warren (Pitkin 1993, 1996). Paromphacodes, Lissochlora and Nemoria cluster together, sharing a bilobed eighth sternite and the presence of a costal sclerite or ornamentation on the valva (Viidalepp 2017). Usually species of Lissochlora have a shorter uncus in the male genitalia than that of related genera, and the last abdominal sternite of the male is usually shorter than the corresponding tergite (Viidalepp 2017).